Solar cell structure and preparation method thereof

By setting a buffer layer in the middle of the polycrystalline silicon or amorphous silicon layer and forming a passivation structure with poor selective thickness by using laser and acid corrosion processes, the problem of difficult to control the thickness uniformity of the polycrystalline silicon or amorphous silicon layer is solved, and the efficiency and stability of the solar cell are improved.

CN119866086APending Publication Date: 2025-04-22DR LASER TECH(WUXI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311326534.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In existing solar cells, the thickness uniformity of the polycrystalline silicon or amorphous silicon layer is difficult to control, resulting in low battery efficiency and high cost.

Method used

By setting a buffer layer in the middle of the polycrystalline silicon or amorphous silicon layer, and selectively removing or modifying the buffer layer and the polycrystalline silicon or amorphous silicon layer by using a laser process, combined with an acid corrosion process, a passivation structure with poor selective thickness is formed.

Benefits of technology

The uniform controllable thickness of polycrystalline silicon or amorphous silicon layer is achieved, which improves battery efficiency and process stability and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119866086A_ABST
    Figure CN119866086A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a solar cell structure, the solar cell structure comprises a passivation structure, and the preparation of the passivation structure comprises the following steps: sequentially forming a first oxide layer, a first polycrystalline silicon or amorphous silicon layer, a buffer layer and a second polycrystalline silicon or amorphous silicon layer on a substrate; confirming a first region and a second region of the first polycrystalline silicon or amorphous silicon layer, and removing the buffer layer and the second polycrystalline silicon or amorphous silicon layer of which the cross section orthographic projection is positioned in the second region of the first polycrystalline silicon or amorphous silicon layer through laser direct removal or laser modification by alkali corrosion; and finally carrying out acid corrosion on the exposed buffer layer. The buffer layer is arranged, so that the thickness of the removed polycrystalline silicon or amorphous silicon layer is uniform and controllable, and the precision is greatly improved; meanwhile, the laser technological process adopted by the invention is easy to implement, low in cost and good in stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solar cells, and in particular relates to a solar cell structure and a preparation method. Background Art

[0002] Due to the explosive growth in solar cell production capacity, improving efficiency and reducing costs is an inevitable trend.

[0003] Usually, efficiency is improved and cost is reduced by improving optical loss, passivation structure, and metallized contact. The existing topcon adopts a tunneling oxide layer + doped poly (polysilicon) passivation contact structure, which allows carriers to pass selectively, thereby reducing recombination and increasing the opening voltage. However, the poly layer itself has the problem of parasitic absorption. The thicker the poly, the more serious the parasitic absorption and the lower the long-wave utilization rate. At present, the thickness of the poly layer is 80nm to 120nm, but if the poly layer is very thin, less than 80nm, it is not compatible with the printing and sintering process. A too thin poly layer will cause the slurry to burn through the back passivation layer. Without burning through, the slurry system cannot form good contact.

[0004] Therefore, the ideal topcon battery back structure has a poly layer thickness of less than 80nm in the non-metallic area. It should be as thin as possible to reduce parasitic absorption while ensuring its passivation effect. The poly layer thickness in the metal contact area is greater than 80nm to match the existing slurry sintering process. Selectively preparing the poly thickness can significantly improve battery efficiency.

[0005] The existing poly thickness selective preparation is generally achieved through the mask + corrosion method. The mask covers the metal contact area to ensure that it is not affected during the corrosion process, and the non-mask covered area is corroded and thinned. However, the disadvantage of this solution is that the thickness of the corrosion area cannot be made uniform and controllable, and the cost is relatively high. The original BOE cleaning needs to be changed to a three-step process of masking, etching, and mask removal. At the same time, the mask is a consumable and the procurement cost fluctuates greatly. Furthermore, there is also a problem of alignment, the accuracy is difficult to further improve, the stability is poor, and the balance between efficiency improvement and cost will be more difficult to control. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a solar cell structure and a preparation method, which can well control the thickness uniformity of the polysilicon or amorphous silicon layer, thereby improving the precision.

[0007] The technical solution adopted by the present invention to solve the above technical problems is: a method for preparing a solar cell structure, wherein the solar cell structure includes a passivation structure, and the passivation structure is obtained by the following steps:

[0008] S1, sequentially forming a first oxide layer, a first polycrystalline silicon or amorphous silicon layer, a buffer layer, and a second polycrystalline silicon or amorphous silicon layer on a substrate;

[0009] S2. Confirm the first region and the second region of the first polycrystalline silicon or amorphous silicon layer, directly remove the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer by laser, and the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is thinned or modified as a laser absorption layer; or, modify the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer by laser and then remove them by alkaline etching, and the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is thinned or retained as an alkaline corrosion barrier layer;

[0010] S3, acid etching, removing the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer, so that the second region of the first polycrystalline silicon or amorphous silicon layer is exposed; the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the first region of the first polycrystalline silicon or amorphous silicon layer cannot be acid-etched and is retained, thereby forming a selective thickness difference.

[0011] According to the above method, the laser directly removes the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second area of ​​the first polycrystalline silicon or amorphous silicon layer. The wavelength of the laser used is 266nm~1500nm, the pulse width is 100fs~10ns, the spot is shaped into Gaussian light or flat-top light, the spot size is 5μm*5μm~800μm*800μm, and the spot energy density is 0.05J / cm2~5J / cm2.

[0012] According to the above method, the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-section is projected in the second area of ​​the first polycrystalline silicon or amorphous silicon layer are modified by laser and then removed by alkaline etching. The wavelength of the laser used is 355nm~1500nm, the pulse width is 1ps~100ns, the spot is shaped into Gaussian light or flat-top light, the spot size is 5μm*5μm~800μm*800μm, and the spot energy density is 0.05J / cm2~2J / cm2.

[0013] According to the above method, in S1, a second oxide layer is formed outside the second polysilicon or amorphous silicon layer;

[0014] In the above S2, when the second polycrystalline silicon or amorphous silicon layer whose cross-sectional orthographic projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is removed, the second oxide layer whose cross-sectional orthographic projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is also removed;

[0015] In the above S3, the second oxide layer whose cross-sectional orthographic projection is located in the first region of the first polysilicon or amorphous silicon layer is also retained.

[0016] According to the above method, the material of the buffer layer is one of silicon oxide, silicon nitride, silicon oxynitride, or one of silicon oxide, silicon nitride, silicon oxynitride doped with elements from Group III, or one of silicon oxide, silicon nitride, silicon oxynitride doped with elements from Group V; the thickness of the buffer layer is 0.5nm to 3nm.

[0017] According to the above method, the material of the buffer layer is one of hafnium oxide, titanium oxide and aluminum oxide; the thickness of the buffer layer is greater than or equal to 0.5 nm.

[0018] According to the above method, the thickness of the second oxide layer is 20-40 nm.

[0019] According to the above method, the thickness of the first oxide layer is 0.5nm-3nm; the thickness of the first polysilicon or amorphous silicon layer is 5nm-40nm; and the thickness of the second polysilicon or amorphous silicon layer is 50-300nm.

[0020] A solar cell structure obtained by using the preparation method of the solar cell structure, the passivation structure comprises a first oxide layer, a first polycrystalline silicon or amorphous silicon layer, a buffer layer and a second polycrystalline silicon or amorphous silicon layer sequentially formed on a substrate; wherein the first polycrystalline silicon or amorphous silicon layer comprises a first region and a second region, and the cross-sectional orthographic projections of the buffer layer and the second polycrystalline silicon or amorphous silicon layer are only located in the first region of the first polycrystalline silicon or amorphous silicon layer, so that the first polycrystalline silicon or amorphous silicon layer in the second region is a thin polycrystalline silicon or amorphous silicon layer, and the first polycrystalline silicon or amorphous silicon layer, the buffer layer and the second polycrystalline silicon or amorphous silicon layer in the first region constitute a thick polycrystalline silicon or amorphous silicon layer as a whole; the thin and thick are both in the cross-sectional direction and are relative concepts.

[0021] According to the above structure, a second oxide layer is formed outside the second polysilicon or amorphous silicon layer.

[0022] The beneficial effects of the present invention are:

[0023] 1. The present invention arranges a buffer layer capable of absorbing laser or blocking alkali corrosion in the middle of the polycrystalline silicon or amorphous silicon layer, and utilizes a laser process to selectively remove a portion of the second polycrystalline silicon or amorphous silicon layer outside the buffer layer directly, or removes it by laser modification and alkali corrosion process, and finally cleans the exposed buffer layer by an acid corrosion process, thereby retaining the second polycrystalline silicon or amorphous silicon layer in the area not processed by the laser, thereby forming a selective thickness difference; the provision of the buffer layer makes the thickness of the removed polycrystalline silicon or amorphous silicon layer uniform and controllable, greatly improving the accuracy; at the same time, the process flow is easy to implement, low in cost, and good in stability.

[0024] 2. The present invention is applicable to all batteries that require a selective thickness difference passivation layer, and is also applicable to batteries that have a second oxide layer formed outside the second polysilicon or amorphous silicon layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a schematic diagram of the battery structure corresponding to step 1 of embodiment 1 of the present invention.

[0026] Figure 2 This is a schematic diagram of the battery structure corresponding to step 2 of embodiment 1 of the present invention.

[0027] Figure 3 This is a schematic diagram of the battery structure corresponding to step three of embodiment one of the present invention.

[0028] Figure 4 This is a schematic diagram of the final structure of the n-topcon battery formed in Example 1 of the present invention.

[0029] Figure 5 This is a schematic diagram of the final structure of the front amorphous silicon passivation contact-back poly passivation contact cell formed in Example 1 of the present invention.

[0030] Figure 6 This is a schematic diagram of the battery structure corresponding to step 1 of embodiment 2 of the present invention.

[0031] Figure 7 This is a schematic diagram of the battery structure corresponding to step 2 of embodiment 2 of the present invention.

[0032] Figure 8 This is a schematic diagram of the battery structure corresponding to step three of embodiment two of the present invention.

[0033] Fig. 9 This is a schematic diagram of the battery structure corresponding to step 4 of embodiment 2 of the present invention.

[0034] In the figure: 101-substrate, 102-first oxide layer, 103-first polysilicon layer, 104-buffer layer, 1041-non-metallic region buffer layer, 105-second polysilicon layer, 106-front aluminum oxide layer, 107-front silicon nitride layer, 108-back silicon nitride layer, 109-front metal contact, 110-back metal contact, 111-front i-amorphous silicon layer, 112-front p-amorphous silicon layer, 113-TCO layer, 114-back silicon nitride layer;

[0035] 201 - substrate, 202 - first oxide layer, 203 - first polysilicon layer, 204 - buffer layer, 205 - second polysilicon layer, 2051 - second polysilicon modified layer, 206 - second oxide layer, 2061 - second oxide modified layer. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a solar cell structure, wherein the solar cell structure comprises a passivation structure, and the passivation structure is obtained by the following steps:

[0037] S1, sequentially forming a first oxide layer, a first polycrystalline silicon or amorphous silicon layer, a buffer layer, and a second polycrystalline silicon or amorphous silicon layer on a substrate;

[0038] S2, confirming the first region and the second region of the first polycrystalline silicon or amorphous silicon layer, directly removing the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer by laser, and the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is thinned or modified as a laser absorption layer; or, modifying the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer by laser and then removing them by alkaline etching, and the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is retained as an alkaline corrosion barrier layer;

[0039] S3, acid etching, removing the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer, so that the second region of the first polycrystalline silicon or amorphous silicon layer is exposed; the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the first region of the first polycrystalline silicon or amorphous silicon layer cannot be acid-etched and is retained, thereby forming a selective thickness difference.

[0040] The solar cell structure is not limited to conventional n-topcon cells, such as p-topcon cells, topcon back junction cells, HJT cells using back poly contacts, and other cells that require selective poly thickness.

[0041] In the passivation structure, a second oxide layer can be formed outside the second polysilicon or amorphous silicon layer, which can be removed together with the second polysilicon or amorphous silicon layer, removed after modification, or retained without affecting the process. Whether there is a second oxide layer depends on the process route, for example, there is no in-situ doping of pecvd.

[0042] The present invention is further described below in conjunction with specific examples and drawings.

[0043] Embodiment 1:

[0044] In the method for preparing the solar cell structure provided in this embodiment, the passivation structure preparation steps are as follows:

[0045] S1, such as Figure 1As shown, a first oxide layer 102, a first polysilicon layer 103, a buffer layer 104 and a second polysilicon layer 105 are sequentially formed on a substrate 101. The buffer layer 104 is used to absorb laser light, thereby blocking the influence of laser light on the first polysilicon layer 103. In this embodiment, the substrate 101 is N-type silicon; the first oxide layer 102 is a tunneling oxide layer, the first oxide layer 102 is silicon oxide, and the thickness is 0.5nm to 3nm; the first polysilicon layer 103 is N-type doped polysilicon, and the thickness is 5nm to 40nm; the buffer layer 104 is titanium oxide, and the thickness is more than 0.5nm. The second polysilicon layer 105 is intrinsic polysilicon, and the thickness is 50 to 300nm.

[0046] S2. Confirm the first area and the second area of ​​the first polysilicon layer 103. Usually, the confirmation is based on the thickness difference area finally formed. The second area is the area where the polysilicon is relatively thin, which is also the non-metal area; the first area is the area where the polysilicon is relatively thick, that is, the metal area. The metal area refers to the area where the electrode is to be printed in the subsequent steps. Because the electrode is metal, it is named the metal area. The non-metal area refers to the area where the electrode does not need to be printed later. The laser directly removes the second polysilicon layer 105 whose cross-sectional projection is located in the second area of ​​the first polysilicon layer, and retains the second polysilicon layer 105 whose cross-sectional projection is located in the first area of ​​the first polysilicon layer.

[0047] In this embodiment, the laser wavelength is 355nm, the pulse width is 10ps, and the spot is shaped into a flat-top light with a shaping lens. The spot size of the flat-top light is 230μm*230μm, and the single pulse energy is 150μJ. The above laser parameters are only for removing a second polysilicon layer 105 of a certain thickness. Other laser parameters that can also achieve the purpose can also be used according to the material, thickness, etc. of the second polysilicon layer and the specific conditions of the laser equipment. Due to material matching issues, the laser range will be relatively wide. Generally speaking, for the purpose of direct removal, the laser wavelength is 266nm~1500nm, the pulse width is 100fs~10ns; the spot is Gaussian light or flat-top light, the spot size is 5μm*5μm~800μm*800μm; the spot energy density is 0.05J / cm2~5J / cm2.

[0048] Under the action of the laser, the buffer layer 104 whose cross-sectional projection is located in the second region of the first polysilicon layer will absorb a portion of the laser energy, thereby being slightly thinned or modified. Figure 2 The non-metal area buffer layer 1041 is formed in the substrate.

[0049] S3. After the laser removes the second polysilicon layer 105, the surface of the exposed non-metallic region buffer layer 1041 is uneven. In order to avoid affecting the subsequent coating process, the non-metallic region buffer layer 1041 is cleaned by acid etching, that is, the cross-sectional projection is located in the buffer layer of the second region of the first polysilicon layer 103. The second polysilicon layer 105 cannot be corroded by acid in the area not acted by the laser.

[0050] The final passivation structure is as follows Figure 3 As shown, it includes a first oxide layer 102, a first polysilicon layer 103, a buffer layer 104 and a second polysilicon layer 105 formed in sequence on a substrate 101; wherein the first polysilicon layer 103 includes a first region and a second region, and the cross-sectional projections of the buffer layer 104 and the second polysilicon layer 105 are only located in the first region of the first polysilicon layer 103, so that the first polysilicon layer 103 in the second region is a thin polysilicon layer, and the first polysilicon layer 103, the buffer layer 104 and the second polysilicon layer 105 in the first region constitute a thick polysilicon layer as a whole; the thin and thick are both in the cross-sectional direction and are relative concepts.

[0051] Through the above process flow, a selective poly thickness difference is formed.

[0052] To achieve the above purpose, the material of the buffer layer 104 needs to be a material that can absorb laser and can be corroded by acid. Its material and thickness can be adjusted according to the laser parameters, so that under the premise of completely removing the second polysilicon layer 105 by laser, a part of the non-metallic area buffer layer 1041 can be retained, as long as the first polysilicon layer 103 is not exposed. In addition, the buffer layer 104 can be a conductive material, or an insulating material that can be controlled to become a tunneling layer. When the buffer layer 104 is a conductive material, it can be one of hafnium oxide, titanium oxide, and aluminum oxide. The thickness is only required to ensure that the first polysilicon layer 103 below is not affected. In this embodiment, the thickness of the buffer layer 104 is greater than or equal to 0.5nm. If the buffer layer 104 is an insulating material, it can be one of silicon oxide, silicon nitride, and silicon oxynitride. In order to improve the absorption effect of the laser, doped silicon oxide, silicon nitride, or silicon oxynitride can also be used, such as silicon oxide, silicon nitride, and silicon oxynitride doped with elements of the III or V main group. The thickness needs to be within a certain range to ensure that it can become a tunneling layer, and can be selected from 0.5nm to 3nm.

[0053] After obtaining the above passivation structure, subsequent processes such as front aluminum oxide passivation, front silicon nitride passivation, back silicon nitride passivation, screen printing slurry, sintering, light injection, testing and sorting are carried out according to the needs of different battery structures to obtain the final battery structure.

[0054] Figure 4A schematic diagram of the final structure of an n-topcon battery formed after a passivation structure is obtained using the present invention is provided. After the above-mentioned passivation structure is obtained on an n-type silicon substrate, a front aluminum oxide layer 106, a front silicon nitride layer 107, and a back silicon nitride layer 108 are further prepared, and then the slurry is screen-printed on both sides to obtain a front metal contact 109 and a back metal contact 110.

[0055] Figure 5 A schematic diagram of the final structure of a front amorphous silicon passivation contact-back poly passivation contact battery is provided after the passivation structure is obtained by using the present invention. After the above passivation structure is obtained on the n-type silicon substrate, the front i-amorphous silicon layer 111, the front p-amorphous silicon layer 112, the TCO layer 113, and the back silicon nitride layer 114 are further prepared, and then the slurry is screen-printed on both sides to obtain the front metal contact 109 and the back metal contact 110.

[0056] The subsequent process flow of each battery is different, but the subsequent process is not protected by the present invention. As long as the battery with the same passivation structure is prepared by the same method as the present invention, it is within the scope of the present invention.

[0057] Embodiment 2

[0058] In the method for preparing the solar cell structure provided in this embodiment, the passivation structure preparation steps are as follows:

[0059] S1, such as Figure 6 As shown, a first oxide layer 202, a first polysilicon layer 203, a buffer layer 204, a second polysilicon layer 205 and a second oxide layer 206 are sequentially formed on a substrate 201. The buffer layer 204 is used to block alkali corrosion and can be one of silicon oxide, silicon nitride, silicon oxynitride, hafnium oxide, titanium oxide and aluminum oxide. Further, when the buffer layer 204 is made of insulating material, it can be used as a tunneling layer. In this embodiment, the substrate 201 is N-type silicon; the first oxide layer 202 is silicon oxide with a thickness of 0.5nm to 3nm; the first polysilicon layer 203 is N-type doped polysilicon with a thickness of 5nm to 40nm; the buffer layer 204 is silicon oxide with a thickness of 0.5nm to 3nm; the second polysilicon layer 205 is N-type doped polysilicon with a thickness of 50 to 300nm; the second oxide layer 206 is PSG with a thickness of 20 to 40nm.

[0060] S2. Confirm the first area and the second area of ​​the first polysilicon layer 203. Usually, the confirmation is based on the thickness difference area formed at the end. The second area is the area where the polysilicon is relatively thin, which is also the non-metal area; the first area is the area where the polysilicon is relatively thick, that is, the metal area. The laser modifies the second oxide layer and the second polysilicon layer located in the second area of ​​the first polysilicon layer 203, that is, Figure 7The second polysilicon modified layer 2051 and the second oxidized modified layer 2061 in the polysilicon layer are preferably more easily corroded by alkali.

[0061] The modification is also called laser surface modification, which is a method of using a laser beam to quickly heat the surface of a workpiece to change the structure of the material surface, thereby changing the physical, chemical and mechanical properties of the material surface.

[0062] In this embodiment, the wavelength of the laser is 532nm, the pulse width is 150ps, and the spot is shaped into a flat top light with a shaping lens. The spot size of the flat top light is 110μm*110μm, and the single pulse energy is 110μJ. The above laser parameters are only for the purpose of modifying the second polysilicon layer and the second oxide layer of a certain thickness. Due to the material matching problem, the laser range will be relatively wide. Generally speaking, for the purpose of laser modification, the wavelength of the laser used is 355nm~1500nm, the pulse width is 1ps~100ns, the spot is shaped into Gaussian light or flat top light, the spot size is 5μm*5μm~800μm*800μm, and the spot energy density is 0.05J / cm2~2J / cm2. Other laser parameters that can achieve the modification purpose can also be selected according to the material of the second polysilicon layer, the thickness of the second polysilicon layer and the second oxide layer, and the specific conditions of the laser equipment.

[0063] S3, alkali etching, removing the second polysilicon modified layer 2051 and the second oxide modified layer 2061. The buffer layer 204 whose cross-sectional projection is located in the second region of the first polysilicon layer, and the second oxide layer 206 whose cross-sectional projection is located in the first region of the first polysilicon layer, cannot be alkali-etched and are retained, thereby forming a selective thickness difference, such as Figure 8 shown.

[0064] Preferably, the material of the buffer layer 204 is silicon oxide, silicon nitride or silicon oxynitride, or silicon oxide, silicon nitride or silicon oxynitride doped with Group III elements, which are not easily corroded by alkali and can be used as an alkali corrosion barrier layer. The laser modified layer is more difficult to corrode than the unmodified layer.

[0065] The material of the buffer layer 204 may also be hafnium oxide, titanium oxide, aluminum oxide, or silicon oxide, silicon nitride or silicon oxynitride doped with a Group V element, which can be slowly corroded by alkali; further, after being modified by laser, it becomes susceptible to alkali corrosion. In this case, the buffer layer 204 needs to be thicker to avoid exposing the first polysilicon layer 203. Similarly, if the material of the buffer layer 204 is silicon oxide, silicon nitride or silicon oxynitride doped with a Group V element, the thickness needs to be controlled to make it a tunneling layer.

[0066] S4. During the laser modification process of step S2, a part of the buffer layer 204 may be modified. The modified buffer layer may become more susceptible to alkali corrosion and be removed by alkali corrosion in S3, leaving a thinned buffer layer. The modified buffer layer may still have good alkali corrosion resistance and thus be retained, and the thinned or retained buffer layer 204 is cleaned by acid corrosion. The second oxide layer 206 whose cross-sectional projection is located in the first region of the first polysilicon layer cannot be corroded by acid.

[0067] The final passivation structure is as follows Fig. 9 As shown, it includes a first oxide layer 202 (i.e., a tunneling oxide layer), a first polysilicon layer 203, a buffer layer 204, a second polysilicon layer 205, and a second oxide layer 206 formed in sequence on a substrate 201; wherein the first polysilicon layer 203 includes a first region and a second region, and the cross-sectional projections of the buffer layer 204, the second polysilicon layer 205, and the second oxide layer 206 are only located in the first region of the first polysilicon layer 203, so that the first polysilicon layer 203 in the second region is a thin polysilicon layer, and the first polysilicon layer 203, the buffer layer 204, the second polysilicon layer 205, and the second oxide layer 206 in the first region constitute a thick polysilicon layer as a whole; the thin and thick are both in the cross-sectional direction and are relative concepts.

[0068] In the above embodiments, the first polycrystalline silicon or amorphous silicon layer, and the second polycrystalline silicon or amorphous silicon layer are described by taking the polycrystalline silicon layer as an example, and the related processes may also use the amorphous silicon layer.

[0069] Through the above process flow, a selective poly thickness difference is formed.

[0070] After obtaining the above passivation structure, subsequent processes such as front aluminum oxide passivation, front silicon nitride passivation, back silicon nitride passivation, screen printing slurry, sintering, light injection, testing and sorting are carried out according to the needs of different battery structures to obtain the final battery structure.

[0071] The subsequent process flow of each battery is different, but they are not protected by the present invention. As long as the battery with the same passivation structure is prepared by the same method as the present invention, it is within the scope of the present invention.

[0072] The mask equipment in the prior art has poor economic efficiency, high cost, requires frequent maintenance, occupies a large area, and has high requirements on the supply side. The present invention uses a buffer layer to block the laser, or blocks the laser + alkali corrosion, and then uses the laser to directly remove it, or laser modification and alkali corrosion to remove it, and finally acid corrosion cleaning, thereby obtaining a passivation structure with poor selectivity and thickness. Compared with the prior art, the laser equipment used in the present invention is easy to operate, stable in operation, has very low maintenance costs, occupies a small area, and only requires power supply and gas.

[0073] The existing mask process has unstable repeatability, low precision, and difficult to guarantee yield, while the laser process of the present invention is controllable, has extremely high repeatability, high precision, and stable yield.

[0074] The existing mask + etching process has poor uniformity and the thickness cannot be accurately controlled. However, the present invention only adds the preparation of a buffer layer to the process, without the need for new equipment, and only requires adjustment of the process, target material, and gas source; adding a buffer layer can greatly improve the stability of the process window and accurately control the selective thinning thickness.

[0075] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing a solar cell structure, characterized in that: The solar cell structure includes a passivation structure, and the passivation structure is obtained by the following steps: S1, sequentially forming a first oxide layer, a first polycrystalline silicon or amorphous silicon layer, a buffer layer, and a second polycrystalline silicon or amorphous silicon layer on a substrate; S2. Confirm the first region and the second region of the first polycrystalline silicon or amorphous silicon layer, directly remove the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer by laser, and the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is thinned or modified as a laser absorption layer; or, modify the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer by laser and then remove them by alkaline etching, and the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is thinned or retained as an alkaline corrosion barrier layer; S3, acid etching, removing the buffer layer whose cross-sectional projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer, so that the second region of the first polycrystalline silicon or amorphous silicon layer is exposed; the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the first region of the first polycrystalline silicon or amorphous silicon layer cannot be acid-etched and is retained, thereby forming a selective thickness difference.

2. The preparation method according to claim 1, characterized in that: The laser directly removes the buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-sectional projection is located in the second area of ​​the first polycrystalline silicon or amorphous silicon layer. The wavelength of the laser used is 266nm~1500nm, the pulse width is 100fs~10ns, the spot is shaped into Gaussian light or flat-top light, the spot size is 5μm*5μm~800μm*800μm, and the spot energy density is 0.05J / cm2~5J / cm2.

3. The preparation method according to claim 1, characterized in that: The buffer layer and the second polycrystalline silicon or amorphous silicon layer whose cross-section is projected in the second area of ​​the first polycrystalline silicon or amorphous silicon layer are modified by laser and then removed by alkali etching. The wavelength of the laser used is 355nm~1500nm, the pulse width is 1ps~100ns, the spot is shaped into Gaussian light or flat-top light, the spot size is 5μm*5μm~800μm*800μm, and the spot energy density is 0.05J / cm2~2J / cm2.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the above-mentioned S1, a second oxide layer is formed outside the second polysilicon or amorphous silicon layer; In the above S2, when the second polycrystalline silicon or amorphous silicon layer whose cross-sectional orthographic projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is removed, the second oxide layer whose cross-sectional orthographic projection is located in the second region of the first polycrystalline silicon or amorphous silicon layer is also removed; In the above S3, the second oxide layer whose cross-sectional orthographic projection is located in the first region of the first polysilicon or amorphous silicon layer is also retained.

5. The preparation method according to any one of claims 1 to 3, characterized in that: The material of the buffer layer is one of silicon oxide, silicon nitride, silicon oxynitride, or one of silicon oxide, silicon nitride, silicon oxynitride doped with elements of the third main group, or one of silicon oxide, silicon nitride, silicon oxynitride doped with elements of the fifth main group; the thickness of the buffer layer is 0.5nm to 3nm.

6. The preparation method according to any one of claims 1 to 3, characterized in that: The material of the buffer layer is one of hafnium oxide, titanium oxide and aluminum oxide; the thickness of the buffer layer is greater than or equal to 0.5 nm.

7. The preparation method according to claim 4, characterized in that: The thickness of the second oxide layer is 20-40 nm.

8. The preparation method according to any one of claims 1 to 3, characterized in that: The thickness of the first oxide layer is 0.5nm-3nm; the thickness of the first polysilicon or amorphous silicon layer is 5nm-40nm; and the thickness of the second polysilicon or amorphous silicon layer is 50-300nm.

9. A solar cell structure obtained by the method for preparing a solar cell structure according to any one of claims 1 to 3, characterized in that: The passivation structure includes a first oxide layer, a first polycrystalline silicon or amorphous silicon layer, a buffer layer and a second polycrystalline silicon or amorphous silicon layer formed in sequence on a substrate; wherein the first polycrystalline silicon or amorphous silicon layer includes a first region and a second region, and the cross-sectional projections of the buffer layer and the second polycrystalline silicon or amorphous silicon layer are only located in the first region of the first polycrystalline silicon or amorphous silicon layer, so that the first polycrystalline silicon or amorphous silicon layer in the second region is a thin polycrystalline silicon or amorphous silicon layer, and the first polycrystalline silicon or amorphous silicon layer, the buffer layer and the second polycrystalline silicon or amorphous silicon layer in the first region constitute a thick polycrystalline silicon or amorphous silicon layer as a whole; the thin and thick are both in the cross-sectional direction and are relative concepts.

10. The solar cell structure according to claim 9, characterized in that: A second oxide layer is formed outside the second polysilicon or amorphous silicon layer.